Pengaruh Intellectual Capital Dan Kepemilikan Manajerial Terhadap Kinerja Keuangan Perusahaan Perusahaan Consumer Goods dan Miscellaneous Industry di Indonesia - Eko Darmawan Suwandi; Akhmad Syarifudin (Jesya, 2026)
This study aims to examine the influence of intellectual capital and managerial ownership on the financial performance of companies listed on the Indonesia Stock Exchange, focusing on the consumer goods and miscellaneous industry sectors during 2017–2022. The study employs a quantitative approach using panel data regression based on financial statements from 50 companies selected through purposive sampling. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC), managerial ownership is measured by the proportion of shares owned by management, while financial performance is proxied by Return on Assets (ROA) and Return on Equity (ROE). The findings indicate that intellectual capital has a positive and significant effect on financial performance, whereas managerial ownership has no significant individual effect. Nevertheless, both variables jointly exert a significant influence on firm financial performance. The novelty of this study lies in integrating the Resource-Based View and Agency Theory to explain the simultaneous role of intellectual capital and managerial ownership using panel data within two strategic manufacturing sectors in Indonesia. This study contributes to the literature by providing empirical evidence that intellectual capital plays a more dominant role than managerial ownership in improving financial performance in emerging market firms and offers managerial implications for strengthening intellectual capital management and corporate governance practices.